Patrimônio cultural de Silveira Martins: proposta de atividades didáticas para Ensino Fundamental, Anos Iniciais - Bianchin, Claudia Moro (2022)
The present Master's dissertation, presented in the Professional Graduate Program in Cultural Heritage, with the following line of research in History and Heritage Education, has o it central objective, to promote the understanding of the concept of Cultural Heritage for students of the 4th year of the School Municipal Elementary School João Frederico Savegnago, based on the implementation of didactic activities, which resulted in a didactic sequence for teachers as a final product. In any case, it is denoted that when developing strategies about Heritage Education, the teacher encourages the student to a journey to the past, which reflects directly in the contemporary context of society, through cultural heritage, legacy and memory. Based on the strategies directly involved, the formation of an awareness aimed at preserving and valuing memory processes automatically makes students capable of exercising citizenship, without the identity of a given community perishing. Consequently, the themes developed and described throughout the didactic sequence, promote a deeper reflection on a knowledge of the true “I”, both by the teacher and by the student, and directly involving the community in general. Such conceptions are based on the essential assumption of belonging and memory, which refer to the ancient legacies left by past generations. In any case, by involving historical aspects and facts, such as Italian immigration, the formation of Silveira Martins-RS and Quarta Colônia, as well as the current Geopark, they are means of reliving the beginning of the organization of society. Everything has a beginning, and this beginning gave rise to the unique identity and “brand” of this community, justifying with this, that other actions are taken into consideration in order to promote a general awareness about the theme of care, appreciation, preservation of the Cultural heritage.